VARIASI DAN FUNGSI BAHASA DALAM JEJARING SOSIAL TWITTER - Yunistita, Yunistita (Humanis; Volume 10. No 2. Februari 2015, 2015)
This research is focused on the variations and functions of language in the social network of twitter. The purpose of this study is (1) to find out the language variations in the social network of twitter, (2) to describe the form of language use in the social network of twitter, and (3) to describe the language functions in the language use of the social network of twitter. The data in this study were analyzed by using the theory of Sociolinguistics and the theory of the Language Structure. The method and technique used in this research were observation method and note-talking technique in obtaining the data, the data analysis was conducted by qualitative method, and the results of data analysis were presented by formal and informal methods. Based on the study, the language variations of the social network of twitter can be divided based on language variation in terms of speakers, the variation in terms of topics and variation in terms of formality and in term of the use of language forms found in the social network of twitter, that there is variation in the level of syntactic grammatical forms, namely the postings contain phrases, clauses, sentences and single sentence, and compound sentence as well as discourse type of exposition. It was also found three language functions in the social network of twitter, i.e. (1) the directive, (2) the expressive and (3) the informative functions.
Keywords: variations and functions of language, grammatical forms.